Masquelet Procedure for the Treatment of Intra-articular Defects of the Wrist - Jawahier, Priscilla A.; Waaijer, Laurien; d'Ailly, Philippe N.; Schep, Niels W.L. (Journal of Wrist Surgery, 2023)
Background The purpose of this case series is to show our experiences with the Masquelet procedure in a variety of infected defects of the wrist.Case Description All consecutive patients that were treated between 2015 and 2021 were included in this case series. Five patients were included with an infected defect of the wrist, involving the radiocarpal and/or the distal radioulnar joints (DRUJ). All patients underwent thorough debridement of the defect and the created void was filled with a gentamicin/vancomycin cement spacer. Cultures were taken and appropriate antibiotic therapy was initiated. Two patients had a renewal of the cement spacer before definitive surgery. Finally, two patients received a DRUJ prosthesis, two patients had autologous bone grafting and wrist arthrodesis and one patient kept the cement spacer as distal ulna prosthesis due to minor complaints.Literature Review Current literature provides examples of the Masquelet procedure in traumatic defects or non-unions of the long bones. These cases are almost always about metaphyseal or diaphyseal defects but rarely include intra-articular joint defects therefore no comparisons could be made between the cases we reported with any existing literature.Clinical Relevance The Masquelet procedure showed to be effective in eradicating infected defects of the wrist involving the radiocarpal joint and/or DRUJ. All patients had an aseptic environment before performing definitive surgery. This technique showed to be save and no reinfections occurred.
Keywords: non-union; infection; Masquelet procedure; arthrodesis; DRUJ prosthesis